Genomic Comparison of Endometrioid Endometrial Carcinoma and Its Precancerous Lesions in Chinese Patients by High-Depth Next Generation Sequencing - Wang, Yao; Yu, Mei; Yang, Jia-Xin; Cao, Dong-Yan; Zhang, Ying; Zhou, Hui-Mei; Yuan, Zhen; Shen, Keng (Frontiers in Oncology, 2019)
Endometrial intraepithelial neoplasia (EIN), also known as endometrial atypical hyperplasia (EAH) is believed to be the precursor lesion of endometrioid endometrial carcinoma (EEC). Many genetic factors play important roles in the process of carcinogenesis, however, the key genetic alterations from dysplasia to endometrial cancer remains poorly understood. Germline mutations in Lynch syndrome genes are associated with hereditary endometrial carcinoma. The role of other cancer susceptibility genes is unclear. The aim of this study was to investigate the genomic alterations of premalignant endometrial lesion and EEC, and to determine the prevalence of cancer predisposition gene mutations in an unselected endometrial carcinoma patient cohort. Here, we applied a comprehensive cancer gene panel (363 cancer-related genes) to capture the exomes of cancer-related genes. Samples were collected from 79 patients with EEC and 36 patients with EIN. Our results demonstrate that EIN harbors most of the driver events reported in EEC and for the first time we reported a high frequency of the amplification of VEGFB gene in endometrial cancer. Moreover, we identified four novel candidate cancer-associated genes (CTCF, ARHGAP35, NF1, and KDR) which may be crucial in the carcinogenesis of EEC. In addition, we identified 2 patients who had a deleterious germline mutation in Lynch syndrome genes (MLH1 and MLH2), and another 8 patients harbored germline mutations of 6 non-Lynch syndrome genes (MUTYH, GALNT12, POLE, MPL, ATM, and ERCC4) which may be associated with endometrial cancer. Larger series will have to be investigated to assess the risks and the proportion of endometrial cancers attributable to other genes.